Ulkus Kronis: Mengenali Ulkus Dekubitus dan Ulkus Diabetikum - Muhammad Hafizh Izuddin Alzamani, Lalu; Rianta Yolanda Marbun, Mona; Eka Purwanti, Mutya; Salsabilla, Rani; Rahmah, Siti (Jurnal Syntax Fusion, 2022)
Chronic ulcers become the factors of morbidity and mortality with an increasing prevalence. The causes of chronic ulcers are venous dysfunction, diabetes mellitus, infection, peripheral neuropathy, stress, and atherosclerosis. Decubitus ulcers are caused by irreversible mechanical pressure on the soft tissue, usually on prominent bones. In addition, the diabetic ulcer is a complication of diabetes mellitus that causes an increase in overall morbidity in patients. Diabetic ulcers can form due to a lack of glycemic control, neuropathy, peripheral vascular disease, or inadequate treatment of wounds on the feet. This article aims to review Chronic Ulcers, specifically Decubitus Ulcers,and Diabeticum Ulcers. Source searches were carried out on online portals for journal publications such as Google Scholar (scholar.google.com) and NCBI (ncbi.nlm.nih.gov), with the keyword Globally, the incidence of pressure ulcers reaches 33% and diabetic ulcers reach 15% of all diabetics. In dealing with chronic ulcers, in general, there is the main principle, namely TIME. The acronym TIME stands for four things to pay attention to, namely: T (Tissue) for a wound that is not feasible or deficient; I (Infection) for with infection/inflammation; M (Moisture) for wound moisture imbalance, which have to be corrected; E (Edge) for a wound where the edge does not cross into it.